Privacy Challenges in Using Wearable Technology in Education Literature Review - Iman Cahyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
His research addresses privacy challenges in the use of educational technology, especially AI and e-learning. The goal is to understand the concept of privacy, educational technology, and related privacy challenges. The literature review method was used to analyze this topic. The results of the study show that the use of educational technology has an impact on user privacy, particularly in the dissemination of personal data, data identification and security, handling of children's data, and data security breaches. The current privacy policy is still limited and there are many challenges that need to be faced, especially in the use of AI and e-learning. Privacy challenges in e-learning include data collection, use of algorithms, and data security breaches. The use of AI also raises privacy challenges, such as facial identification and automated decision making